THE PRACTICE OF VALUES AND BEHAVIORAL PROBLEMS IN STUDENTS - Chunga Romero, Aminta Lourdes (International Journal of Psychosocial Rehabilitation, 2020)
Values are an inherent expression of human beings and are present everywhere including all actions and thoughts, these are essential for the subsistence of man, keep in mind the values, being a topic of debate in recent years, especially in the school and academic environment, where their importance is analyzed, for the successful fulfillment of activities in the educational field. The purpose of this research work is to identify the influence of the practice of values on the behavioral problems of the students of the Pichincha Fiscal Basic Education School, located in the canton May 24, in the province of Manabí, especially at the levels of the basic elementary and middle. The qualitative transversal methodology was applied using a structured survey, a bibliographic review aimed at defining the importance of values in the educational process. The investigation showed that students have behavioral problems due to the inadequacy of the practice of values, affecting school life.